2022
DOI: 10.3389/fpls.2022.1049015
|View full text |Cite
|
Sign up to set email alerts
|

Five new secondary metabolites from an endophytic fungus Phomopsis sp. SZSJ-7B

Abstract: Two previously undescribed lactones, phomolides A and B (1 and 2), and three new sesquiterpenoids, phomenes A–C (3–5), together with one known compound, colletotricholide A (6), were isolated from the endophytic fungus Phomopsis sp. SZSJ-7B. Their chemical structures, including the absolute configurations, were comprehensively established by extensive analyses of NMR, high-resolution electrospray ionization mass spectrometry, electronic circular dichroism powered by theoretical calculations, and X-ray diffract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 78 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…According to the literature investigation, [34][35][36][37] different active chemicals, such as sesquiterpenoids, steroids, isocoumarin, cytochalasins, xanthonesun, and precedented carbon skeletons, have been discovered in specialized metabolites of the fungi Phomopsis sp., and the number and variety of specialized metabolites from the fungal genus Phomopsis are still increasing. However, the identified structures in this study are quite different from the structures reported in the literature because of the fermentation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature investigation, [34][35][36][37] different active chemicals, such as sesquiterpenoids, steroids, isocoumarin, cytochalasins, xanthonesun, and precedented carbon skeletons, have been discovered in specialized metabolites of the fungi Phomopsis sp., and the number and variety of specialized metabolites from the fungal genus Phomopsis are still increasing. However, the identified structures in this study are quite different from the structures reported in the literature because of the fermentation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The conformation search and optimization, DFT GIAO 13 C NMR, and ECD calculations of compounds 1 and 2 were performed as previously described [40]. The detailed computational method, DFT optimized geometry data, relative energies, and conformational population of all calculated structures were attached in the Additional file 1.…”
Section: Fungal Materialsmentioning
confidence: 99%
“…In our ongoing research program focusing on the discovery of biologically meaningful natural products with unique structures from plant-originated fungi [32][33][34][35][36][37][38][39][40], the strain of Trichoderma koningiopsis SC-5 derived from Pedicularis integrifolia was experimentally revealed to produce abundant structurally diverse secondary metabolites as referring to the TLC and HPLC-DAD analyses. The further detailed chemical investigation of Trichoderma koningiopsis SC-5 had led to the isolation of two fascinating koninginin derivatives -koningipyridines A and B (1 and 2), which featured an unprecedented pentacyclic ketal skeleton with the formation of a complex 6/6/5/6/5 fused ring system and a unique 6/6/5 dihydropyridine skeleton, respectively (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…During our continuing search for novel microbial natural products [23][24][25][26][27], we have previously reported two novel koninginin derivatives sharing unprecedented nitrogenous fused polycyclic polyketide skeletons from Trichoderma koningiopsis SC-5 [28]. With the examination of other similar structurally unique and biologically meaningful koninginins, the further chemical investigation of Trichoderma koningiopsis SC-5 successfully led to the the examination of other similar structurally unique and biologically meaningful koninginins, the further chemical investigation of Trichoderma koningiopsis SC-5 successfully led to the isolation of three novel koninginin derivatives, koninginins X-Z (1-3) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%